Photographs and archival documents and their role in diagnosing the manifestations of damage rock engravings and ways of limiting "Models of the Saharan Atlas" - ben seghier, Nawal; aissaoui, Bouakaz (The Algerian Historical Journal, 2026)
During the past century, the Saharan Atlas region has witnessed several discoveries of rock art sites by French military campaigns in Algeria, with a series of studies, inventory photos and maps. And the importance to diagnosing and preserving the petroglyphs Based on taking some models from models from rock-engraving stations, and on collecting the results reached through photographs and archival documents of researchers. This study relied on collecting and copying some photos and documents and employing them in the analytical and descriptive study in order to diagnose the manifestations of their damage and reduce their deterioration by applying the preventive maintenance approach to preserve this cultural